ACQUISITION OF YOUTH LIFE SKILLS - Anita Lidaka; Svetlana Lanka (European Scientific Journal, ESJ, 2014)
A successful life position for any person is based on different types of knowledge and their acquisition and enrichment probability; awareness of own abilities, their development and personal interest in the process; a system of positive attitudes as an integrated wholeness of personality traits which are formed in life experience, knowledge acquisition and will effort unit and are manifested in values, goals, ideals and norms. Successful role performance guarantees confident young people‘s functioning in the society, thereby creating the sense of security and confidence in themselves and their actions. In order to fulfil social roles it is necessary to acquire the general, social, as well as personal skills, which are generally referred to as life skills. If they are acquired successfully, young people are able to build successful relationships with their peers and also adults, are able to be active members of social life. Life skills guarantee success to young people in their personal life formation. They are able to be more independent and also be responsible for their actions and take responsibility for it. Thus one of the school tasks is to promote the pupils‘ personal and social development. I Rubane (Rubane, 2000) has acknowledged self-cognition and self-determination, awareness and defence of own rights, stress management, resistance to psychological pressure, critical thinking, decision making, problem solution, social adaptation , cooperation, efficient communication asimportant life skills. However, the mentioned life skills can be called as important only conditionally, for no personal skills are mentioned what the young people could find a solution to different life situations with. These skills include self-care, cooking, personal budgeting, housework performance, usage of home/office appliances, daily routine planning, healthy lifestyle adherence etc.